Cloning of reiterated and nonreiterated herpes simplex virus 1 sequences as BamHI fragments. - Post, L E (1980)
Over 95% of the herpes simplex virus type 1 (strain F) DNA sequences have been cloned as BamHI fragments in the pBR322 plasmid. With one exception, all of the cloned fragments have the same electrophoretic mobilities and restriction enzyme cleavage sites as do the authentic fragments derived from the BamHI digests of the viral genome. The exception is the BamHI B fragment mapping at the right end of L component in the prototype arrangement of the DNA. Thus, a small deletion mapping near the left end of the fragment was present in two independently derived plasmids. Included in the collection of plasmids are several clones containing DNA sequences that span the junction between the L and S components of the virus DNA. Several plasmids containing the junction fragment were found to be sufficiently stable to permit the preparation of large amounts of the DNA fragment for fine-structure mapping of the restriction enzyme cleavage sites. Preliminary studies on one cloned fragment (BamHI G) have shown that it is biologically active in marker rescue of a temperature-sensitive mutation and in transfer of a plaque morphology marker.